1992
DOI: 10.1093/jmedent/29.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Release of Mesocyclops aspericornis (Copepoda) for Control of Larval Aedes polynesiensis (Diptera: Culicidae) in Land Crab Burrows on an Atoll of French Polynesia

Abstract: On Tereia Island, Rangiroa Atoll, 14,321 land crab burrows were treated with the copepod Mesocyclops aspericornis from January to June 1986, to control larvae of Aedes polynesiensis marks. In October 1987, the entire island of Tereia was retreated (17,300 burrows), and the neighboring island, Voisin, was left untreated as a control. From 5 to 15 mo after treatment, burrows with M. aspericornis contained an average of 2 Ae. polynesiensis immatures compared with 97 immatures from untreated burrows. Long-term lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 5 publications
0
36
0
Order By: Relevance
“…According to Lardeux et al [25] , M. aspericornis served as a good biocontrol agent against Ae. aegypti within a three-weeks time period whereas the maximum predatory capacity of M. apericornis was found to be 49.3 (mean value) and the minimum 39.3.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lardeux et al [25] , M. aspericornis served as a good biocontrol agent against Ae. aegypti within a three-weeks time period whereas the maximum predatory capacity of M. apericornis was found to be 49.3 (mean value) and the minimum 39.3.…”
Section: Discussionmentioning
confidence: 99%
“…M. aspericornis is a widely distributed species known to control several mosquito species. Surveys have shown that M. aspericornis is abundant in natural freshwater sources (Lardeux et al, 1992;Russell et al, 1996;Nam et al, 2000) M. aspericornis is a dominant species found in artesian wells and peridomestic containers in eastern Thailand. It has been shown to be an effective predator of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Similar investigations have also been done using Mesocyclops spp. in conjunction with other controlling methods and resulting in eradication mosquitoes [35][36][37][38] . Larvivorous copepods such as Macrocyclops albidus, M. longisetus and Mesocyclops aspericornis are highly effective for controlling Aedes sp.…”
Section: Discussionmentioning
confidence: 99%
“…culicifacies larvae was assessed by placing single adult copepod in tissue culture plate wells (35 mm diameter, 18 mm depth) with newly hatched first instar larvae in the laboratory condition. The predatory nature and the rate of predatory efficiency of adult M. longisetus on mosquito larvae were observed under a stereomicroscope.…”
Section: Copepod On Larval Instars Predatory Efficiency Testmentioning
confidence: 99%